Alga‐Made Anti‐Hepatitis B Antibody Binds to Human Fcγ Receptors. Issue 4 (27th December 2017) - Vanier, Gaëtan; Stelter, Szymon; Vanier, Jessica; Hempel, Franziska; Maier, Uwe G.; Lerouge, Patrice; Ma, Julian; Bardor, Muriel
Abstract : Microalgae are unicellular eukaryotic organisms which represent an emerging alternative to other cell biofactories commonly used to produce monoclonal antibodies. Microalgae display several biotechnological advantages such as their rapid growth rate and their phototrophic lifestyle allowing low production costs as protein expression is solar‐fueled. Recently, a fully assembled recombinant IgG antibody directed against Hepatitis B surface antigen is produced and secreted in the culture medium of the diatom Phaeodactylum tricornutum . A biochemical characterization of this recombinant antibody demonstrated that the Asn‐297 is N ‐glycosylated by oligomannosides. In the immune system, antibodies interact with effector molecules and cells through their Fc part and the recognition of Fcγ receptors (FcγR) which are important for inducing phagocytosis of opsonized microbes. Interactions between IgG and FcγR are influenced by the N ‐glycan structures present on the Asn‐297. In this study, the authors characterized the binding capacity of the anti‐hepatitis B recombinant IgG produced in P. tricornutum to two human Fcγ receptors (FcγRI and IIIa) using a cellular binding assay and surface plasmon resonance (SPR). This allowed us to demonstrate that the alga‐made antibody is able to bind FcγRI with a reduced affinity and engages FcyRIIIa with 3‐times higher affinity compared to a control human IgG1. Abstract : Recombinant monoclonal antibodies such as the human anti‐Hepatitis B antibody produced in the diatom Phaeodactylum tricornutum, are able to bind to human Fcγ Receptors presents at the surface of human cells. This suggest that such alga‐made antibodies could be efficient in human therapy and reinforce the potential of microalgae as an alternative expression system for the production of biopharmaceuticals.